Accelerator-based BNCT - Kreiner, Andres Juan (2013)
The activity in accelerator development for accelerator-based BNCT(AB-BNCT)both world wide and in Argentina is described.Projects in Russia, UK, Italy, Japan, Israel, and Argentina to develop AB-BNCT around different types of accelerators are briefly presented.In particular,the present status and recent progress of the Argentine project will be reviewed. The topics will cover:intense ion sources,accelerator tubes, transport of intense beams,beam diagnostics,the 9Be(d,n) reaction as a possible neutron source, Beam Shaping Assemblies(BSA),a treatment room,and treatment planning in realistic cases.